EFEKTIVITAS PEMBELAJARAN ONLINE PADA MASA PANDEMI COVID-19 - Lenggasari Pohan; Nurfajriani Nurfajriani; Retno Dwi Suyanti; Siti Khodijah Dalimunthe (PROSIDING SEMINAR KIMIA, 2022)
Research has been carried out on "The Effectiveness of Online Learning During the Covid-19 Pandemic" at SMAN 1 Binjai Kuala Begumit for the 2020/2021 Academic Year. This study aims to determine student activities, to use online learning media and to find out the benefits of online learning. Research methods This type of research is included in qualitative research. Where in this study using a study of literature, journals, books. This study uses a survey method conducted online. Data were collected using the saturated sample method, where the entire population was sampled.Data collection was carried out by distributing online questionnaires to 35 respondents as a sample consisting of school teachers at SMAN 1 Binjai Kuala Begumit who conducted online learning. Collecting data using a questionnaire is used to get responses from respondents. Based on the research results obtained from respondents' answers, it shows that: 58% of respondents are ready to follow changes and support government directives to implement online learning. 40% of respondents are happy to use online learning media. 20% of respondents support if this online learning system is implemented in the future. 25% of respondents stated that online learning was effective in improving student learning outcomes. Keywords: Online learning, Pandemic Period.